2020
DOI: 10.14738/assrj.79.8958
|View full text |Cite
|
Sign up to set email alerts
|

Shariah Information Disclosure and its Effect on Financial Perfomance among SMEs in Malaysia

Abstract: Introduction: Shariah disclosure has become an important aspect in a Small-Medium Enterprises (SMEs). The disclosure of shariah information would enhance the transparency and accountability of SMEs towards its stakeholders which in return helps promote the long-term profitability and sustainability. Objective: (1) examine the extensiveness of Shariah disclosure and (2) investigate the relationship between Shariah disclosure on product and services, financing, earnings and expenditure, social functions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In developing economies, the rate of information disclosures was not significant on profitability and market value indicators for listed companies (Dagilienė, 2013). Azman et al. (2020) concluded that the sustainability dimension of information disclosures was insignificant on SMEs' performance.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In developing economies, the rate of information disclosures was not significant on profitability and market value indicators for listed companies (Dagilienė, 2013). Azman et al. (2020) concluded that the sustainability dimension of information disclosures was insignificant on SMEs' performance.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In developing economies, the rate of information disclosures was not significant on profitability and market value indicators for listed companies (Dagilien_ e, 2013). Azman et al (2020) concluded that the sustainability dimension of information disclosures was insignificant on SMEs' performance. Finally, Abba et al (2018) detected no statistical evidence supporting the association between disclosure quality and performance of listed firms from Nigeria.…”
Section: Information Disclosuresmentioning
confidence: 99%
“…, 2008). Lastly, some literature concludes that DISC is statistically insignificant in SMEs’ FP (Azman et al. , 2020).…”
Section: Literaturementioning
confidence: 98%
“…Conversely, several other studies provide conflicting testimony claiming a negative impact of the DISC on the FP (Dagilien_ e, 2013; Haat et al, 2008). Lastly, some literature concludes that DISC is statistically insignificant in SMEs' FP (Azman et al, 2020).…”
Section: Information Disclosures (Disc)mentioning
confidence: 98%